Pengembangan Instrumen Evaluasi Pembelajaran Pendidikan Agama Buddha Jenjang SMA Berbasis Kontekstual Dan Hots Pada Kurikulum Merdeka Dengan Pendekatan Metode Pilihan Ganda Kompleks - Leo Nando Sastro; Sobani Sobani; Shintia Greshia; Yani Relita Sulandari; Juwita Ratna Dewi; Ryan Gautama; Kemanya Karbono; Puji Sulani (JURNAL MANAJEMEN PENDIDIKAN, 2026)
DEVELOPMENT OF A CONTEXTUAL AND HOTS-BASED EVALUATION INSTRUMENT FOR BUDDHIST RELIGIOUS EDUCATION LEARNING AT HIGH SCHOOL LEVEL IN THE INDEPENDENT CURRICULUM WITH A COMPLEX MULTIPLE CHOICE METHOD APPROACH Abstract. This study aimed to develop and validate a contextual Higher Order Thinking Skills (HOTS)-based evaluation instrument using complex multiple-choice items to measure the spiritual attitudes of Grade XI students in Buddhist Education under the Merdeka Curriculum. The research employed a Research and Development (R&D) approach with the ADDIE model involving 45 students and expert validators. Instrument quality was evaluated using the Rasch model, including reliability, construct validity, dimensionality, item fit, and Differential Item Functioning (DIF). The results demonstrated satisfactory psychometric properties, with person reliability of 0.77, item reliability of 0.98, and overall reliability of 0.89. Construct validity was confirmed through a Raw Variance Explained of 77.2%, while only one item exhibited gender bias. The developed instrument effectively measures higher-order thinking at the analysis and evaluation levels within authentic learning contexts and is suitable for assessing students' spiritual attitudes in Buddhist Education.